A novel CEP57 variant associated with mosaic variegated aneuploidy syndrome in a Chinese female presenting with short stature, microcephaly, brachydactyly, and small teeth. Issue 6 (17th April 2022) - Feng, Biyun; Chang, Guoying; Zhang, Qianwen; Li, Xin; Tang, Yijun; Gu, Shili; Wang, Yirou; Wang, Jian; Wang, Xiumin
Abstract: Background: Mosaic variegated aneuploidy (MVA) syndrome is a rare, autosomal recessive genetic disease. Here, we report an ultra‐rare case of MVA syndrome associated with a CEP57 variant. Methods: We retrospectively analyzed the clinical data of a 9‐year‐old female patient and surveyed her family members. Whole‐exome sequencing and karyotype analysis were performed; suspected mutations were verified using Sanger sequencing. Results: The patient presented with intrauterine growth restriction, short stature, microcephaly, facial dysmorphism, brachydactyly, and small teeth, and she showed unsatisfactory response to GH replacement therapy. Laboratory tests revealed high insulin‐like growth factor‐1 levels. Karyotype analysis of the peripheral blood showed mosaic variegated aneuploidies. Whole‐exome and Sanger sequencing revealed a novel homozygous nonsense variant, NM_014679.4: c.312 T > G, in CEP57 that leads to translation termination (p.Tyr104*). The parents were heterozygous carriers of the identified variant. Conclusion: This study presents an ultra‐rare case of CEP57‐ driven MVA syndrome, identifying a novel homozygous nonsense variant of CEP57 (p.Tyr104*). Our findings enrich the CEP57 mutational spectrum and emphasize the importance of genetic testing in patients with microcephaly and short stature. Furthermore, we conclude that growth hormone treatment is ineffective in such patients. Abstract : The study presents the first reported Chinese case of CEP57‐driven MVA, which revealed a novel homozygous nonsense variant of the CEP57 gene (p.Tyr104*). The proband presents with intrauterine growth restriction, short stature, microcephaly, facial dysmorphism, brachydactyly, and dental dysplasia, whose height did not change after growth hormone treatment.